A continuum of solutions for the SU(3) Toda System exhibiting partial blow‐up. Issue 4 (7th September 2015) - D'Aprile, Teresa; Pistoia, Angela; Ruiz, David
Abstract : In this paper, we consider the so‐called Toda System in planar domains under Dirichlet boundary condition. We show the existence of continua of solutions for which one component is blowing‐up at a certain number of points. The proofs use singular perturbation methods.